2016
DOI: 10.1007/s00415-016-8309-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain plasticity in Parkinson’s disease with freezing of gait induced by action observation training

Abstract: Gait disorders represent a therapeutic challenge in Parkinson's disease (PD). This study investigated the efficacy of 4-week action observation training (AOT) on disease severity, freezing of gait and motor abilities in PD, and evaluated treatment-related brain functional changes. 25 PD patients with freezing of gait were randomized into two groups: AOT (action observation combined with practicing the observed actions) and "Landscape" (same physical training combined with landscape-videos observation). At base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
186
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(215 citation statements)
references
References 49 publications
7
186
3
1
Order By: Relevance
“…Furthermore, the presence of a human model in the virtual walking scenarios makes the imagery task more visually guided and less internally driven, with less need for the activation of subcortical areas such as the MLR. While clinical studies indicate that action observation is successful in defreezing patients with difficulties in gait initiation and maintenance [Agosta et al, ; Pelosin et al, ], our data suggest that full‐blown gait imagery recruits the gait motor network more extensively. Thus, while gait observation may best aid gait rehabilitation in patients with impaired functioning of brainstem centers, motor imagery could be particularly beneficial in those presenting no neurological dysfunction in subcortical areas, for instance, in patients with a functional limitation of locomotion of peripheral origin, as in orthopedic patients.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, the presence of a human model in the virtual walking scenarios makes the imagery task more visually guided and less internally driven, with less need for the activation of subcortical areas such as the MLR. While clinical studies indicate that action observation is successful in defreezing patients with difficulties in gait initiation and maintenance [Agosta et al, ; Pelosin et al, ], our data suggest that full‐blown gait imagery recruits the gait motor network more extensively. Thus, while gait observation may best aid gait rehabilitation in patients with impaired functioning of brainstem centers, motor imagery could be particularly beneficial in those presenting no neurological dysfunction in subcortical areas, for instance, in patients with a functional limitation of locomotion of peripheral origin, as in orthopedic patients.…”
Section: Discussioncontrasting
confidence: 58%
“…Apart from cues, treadmill training [164][165][166][167][168], obstacle aquatic training [169], supervised slackline training [170], walk-bicycle [171], and action observation [172,173] have also shown positive effects on FOG. Recently, Cosentino C et al [174] performed a systematic review and metaanalysis to evaluate the effectiveness of physiotherapy intervention on FOG symptoms.…”
Section: Physiotherapymentioning
confidence: 99%
“…In the study, the authors compared an experimental group who observed video clips showing specific movements and strategies to circumvent freezing of gait episodes and controls who observed a landscape scene in addition to routine physical therapy three times a week, for four weeks. Similarly, Agosta and colleagues [28] examined the efficacy of action observation training on disease symptoms, freezing of gait and motor abilities in Parkinson's disease. Patients were randomised into two groups, an experimental group who observed the gait of an actor over four weeks in addition to physical training and a control group who observed a landscape video in addition to physical training.…”
Section: Parkinson's Diseasementioning
confidence: 99%